The effect of patent litigation insurance: Theory and evidence from NPEs - Bernhard Ganglmair; Christian Helmers; Brian J. Love (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2020)
We analyze the extent to which private defensive litigation insurance deters patent assertion by non-practicing entities (NPEs). We study the effect that a patent-specific defensive insurance product, offered by a leading litigation insurer, had on the litigation behavior of insured patents' owners, all of which are NPEs. We first model the impact of defensive litigation insurance on the behavior of patent enforcers and accused infringers. We show that the availability of defensive litigation insurance can have an effect on how often patent enforcers will assert their patents. We confirm this result empirically showing that the insurance policy had a large, negative effect on the likelihood that a patent included in the policy was subsequently asserted relative to other patents held by the same NPEs and relative to patents held by other NPEs with portfolios that were entirely excluded from the insurance product. Our findings suggest that market-based mechanisms can deter so-called "patent trolling."
Keywords: G22; K41; O34; 330; NPEs; patents; insurance; litigation